1998
DOI: 10.1083/jcb.140.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free Transport to Distinct Golgi Cisternae Is Compartment Specific and ARF Independent

Abstract: The small GTPase ADP-ribosylation factor (ARF) is absolutely required for coatomer vesicle formation on Golgi membranes but not for anterograde transport to the medial-Golgi in a mammalian in vitro transport system. This might indicate that the in vivo mechanism of intra-Golgi transport is not faithfully reproduced in vitro, or that intra-Golgi transport occurs by a nonvesicular mechanism. As one approach to distinguishing between these possibilities, we have characterized two additional cell-free systems that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 64 publications
(125 reference statements)
4
51
1
Order By: Relevance
“…We have previously reported that incubation of Golgi membranes with ARF-depleted cytosol causes an increase in the average size of cisternal fenestrae and a modest increase in their number (23). In the current study, this observation has been confirmed and extended.…”
Section: Arf Coatomer and The Regulation Of Cisternal Morphologysupporting
confidence: 88%
See 4 more Smart Citations
“…We have previously reported that incubation of Golgi membranes with ARF-depleted cytosol causes an increase in the average size of cisternal fenestrae and a modest increase in their number (23). In the current study, this observation has been confirmed and extended.…”
Section: Arf Coatomer and The Regulation Of Cisternal Morphologysupporting
confidence: 88%
“…From these data, we estimate that the concentration of coatomer in a standard transport reaction containing 5 ml of Golgi and 2.5-10 ml of cytosol is 1 -3.6 mg/ml in reactions containing mockdepleted cytosol, and is B0.08 -0.24 mg/ml in reactions containing coatomer-depleted cytosol. For comparison, cytosol depleted of \ 95% of the endogenous ARF was also prepared by ion-exchange chromatography, as previously described (23).…”
Section: Gtp S Inhibits Transport Without Coatomer Recruitmentmentioning
confidence: 99%
See 3 more Smart Citations